Influence of Crushed Brick Columns on Geotechnical Properties of Expansive Soil - Ng, Jun Shen; Muzamir, Hasan; Low, Yong Ler (Penerbit Universiti Teknologi Malaysia, 2024)
Utilization of crushed brick which is a common industrial material that is potentially wasted during the construction process in ground improvement can relieve its detrimental effects on the environment thereby reducing the waste disposal challenges. Hence, this study proposes its utilization as reinforcement to the soft clay soil. The tests mainly focused on the particle size distribution (PSD), specific gravity, Atterberg limit, proctor analysis as well as the shear strength parameters from Unconfined Compression Test (UCT). Coherently, the vibro-replacement method was deployed within a small-scale laboratory approach as a prediction model for the construction of a group of crushed brick columns. The column design was mainly classified into partially penetrated columns which have 60 mm and 80 mm height, and fully penetrated columns with 100 mm height. The mass of crushed brick used was approximately 1.07% - 4.56% of its total mass of specimen which produces the shear strength improvement rate from 11.00% - 18.55%. From the obtained results, the use of fully penetrated 100 mm diameter columns enhanced the undrained shear strength of kaolin clay to the maximum value, 26.20kPa or 18.55% as compared to the control sample with no reinforcement, which reduced the soil settlement and promoted the use of sustainable material in ground improvement.